Synchronous Control of a Dual-Motor Driving Rack and Pinion Module for Steer-by-Wire System - Insu Chung; Sehoon Oh; Kanghyun Nam (IEEE Access)
Synchronous control of multi-motor systems (MMS) is attracting attention as a method to achieve the objectives of accurate operation, load distribution, vibration, and noise reduction while responding to the demands of large forces, high speed, etc. in industrial sites. The performance of synchronous control is evaluated by command tracking and synchronization between motors. In order to improve these two goals, the existing synchronous control structures mainly designed controllers in the case of command tracking, and synchronization between motors used a compensation method using synchronous error. However, this method makes it difficult to analyze or control the level of synchronous error. This paper presents a novel control structure that directly controls tracking commands and synchronous errors by setting the input and output mean and differences of MMS as control targets. The model applying the proposed structure can reduce the resonance due to the combined compliance of the MMS in the input and output relationship, which has been validated by the experimentally measured frequency response function. In addition, experiments were conducted to verify the effectiveness of synchronous control performance when the proposed control structure was applied. The algorithm was constructed using Matlab/Simulink, and the actual equipment was controlled using a data acquisition (DAQ) board. In order to compare the existing synchronous control structures with the proposed control structure, a model-based controller based on dynamic analysis was designed, and the results were derived through two commands. Through this, it was verified that the proposed control structure can improve synchronous control performance.